Energy supplementation of steers grazing early-season, native range: effects on grazing and subsequent finishing performance and carcass merit - Sean P. Montgomery; R.L. Packard; J.C. Forcherio; R.R. Scott; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2003)
Crossbred beef steers (n = 328, initially 495 lb) were used to determine the effects of energy supplementation on grazing and subsequent finishing performance of steers grazing early-season, native range. Treatments consisted of either no supplemental energy or access to feeders containing a free choice, grain-based energy supplement. On the first day of the grazing period, steers were weighed and randomly allotted among eight pastures, providing four replications per treatment. Stocking density was 34% higher for supplemented than for unsupplemented pastures. At the end of the grazing period, steers were transported to a commercial feedlot and allowed ad libitum access to a common finishing diet for an average of 171 days. Supplement intake averaged 5.4 ± 1.1 lb/day (dry matter basis) or approximately 0.90% of body weight during the grazing period. Supplementation increased (P<0.01) grazing period gains from 1.47 to 2.20 lb/day. Supplementation also increased (P<0.01) ribeye area, back fat, and rump fat at the end of the grazing period. Supplementation did not affect subsequent finishing performance or carcass merit, but it reduced (P<0.01) time required for finishing by 18 days. Energy supplementation of steers grazing early-season, native range resulted in more pounds of gain per acre due to improved grazing performance as well as a 34% increase in stocking density.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Energy; Steers; Finishing performance; Carcass merit